Istiratijiyyat Ta’lim al-Lughah al-‘Arabiyyah ‘Ala Asas Takamul al-Manhaj fi Dhu’i Tashnif Bloom - Febriani, Suci Ramadhanti; Asrori, Imam; Sutaman, Sutaman; Guettaoui, Kddour Bedra (Institut Agama Islam Negeri Curup, 2023)
This research aimed to analyze Arabic language learning strategies based on curriculum integration from the perspective of Bloom's Taxonomy at Diniyah Puteri Islamic Boarding School. A qualitative approach with a case study method was used in this study. Data collection techniques included interviews with Arabic teachers, the headmaster, and the head of the Diniyyah Arabic Center (DAC). Other data collection techniques subsumed observation of learning activities and documentation from curriculum and lesson plans. The authors used Miles and Hubberman’s analysis theory to analyze the data. The substantive findings of this study showed that Arabic learning strategies based on integration of the Ministry of Religion's curriculum and the Diniyyah Arabic Center (DAC) from the perspective of Bloom's Taxonomy fell into the following: (a) the stages of remembering consisted of remembering pearls in the language environment, memorizing daily vocabulary, and memorizing conversations; (b) the stages of understanding consisted of listening to Arabic announcement strategies and using reading and translating methods; (c) the implementation stage consisted of Nasyaat Al-Akbaar, comparative studies, direct strategies, listening and speaking strategies; and (d) the creating stage consisted of Arabic camps, composing songs, and weekly speeches. The findings of this study infer that curriculum integration provides opportunities for students to improve Arabic language skills with varied strategies.